The Effect of Visionary School Principal Leadership and Organizational Culture on Teacher Performance in Junior High Schools - Muhtasor Muhtasor; Hasan Hariri; Sowiyah Sowiyah; Handoko Handoko (Edumaspul: Jurnal Pendidikan, 2025)
The purpose of this study was to examine the partial effects of visionary school leadership and organizational culture on teacher performance. This study used a quantitative approach. The population of this study consisted of all junior high school teachers in Pringsewu Regency, Lampung Province, totaling 822 teachers. From this population, a sample of 274 teachers was selected using proportional random sampling. Data collection was conducted by distributing questionnaires using a five-point Likert scale. The data analysis technique used in this study was simple regression. The results showed that the direct influence of visionary leadership on teacher performance was 77.8%. Meanwhile, the direct influence of organizational culture on teacher performance was 74.5%. Further research is recommended to expand the sample and use a qualitative approach to obtain more in-depth results.